Ecoliterature in the Context of Animal Studies and the Ethical Turn - Szalewska, Katarzyna (Porównania, 2022)
The article is an attempt to read various types of journalism that deal with human-animal relations (“Wolves” by Adam Wajrak and “Un chien mort après lui” by Jean Rolin). Each of these texts covers a different category in which we classify animals (wild, companion), but the authors deconstruct these categories. Thanks to this, the interpretation of the aforementioned books has also contributed to the development of such issues as “wildness,” empathy in human-animal relations, cultural conditions of treating certain animal species, species chauvinism, etc. These considerations were obviously included in the spirit of posthumanism, but most of all the ethical turn. The introduction includes, in turn, reflections on the particular genre, which is nature writing, and its evolution in the context of changes that took place in humanistic thought (e.g. negating the division into nature and culture).